The Effectiveness of Kahoot Game in Improving Students' Vocabulary Mastery - Zulfirah, Wulan; Darmawan, Darmawan; Maf'ulah, Maf'ulah (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2023)
The objective of this research is to find out if the use of Kahoot Game can improve students’ vocabulary mastery of SMA Negeri 8 Palu. This research used quasi-experimental design that consisted of two groups; experimental and control group. The samples of this research was the eleventh grade students of SMA Negeri 8 Palu; IPA 2 with 27 students as the experimental group and IPA 3 with 25 students as the control group that selected by using purposive sampling. The data was collected by administering test consisted of a pre-test and post-test that conducted at first and last meetings. Then the treatment was only given to the experimental group. The result of experimental group’s pre-test is 39.44, while control group is 34.6. The result of experimental group’s post-test is 77.03, while control group is 61.2. By applying 0.05 level of significance, the researcher found that the value of the t-counted (3.31) is higher than the t-table (1.677). In conclusion, the use of Kahoot Game in teaching vocabulary is effective to improve students’ vocabulary mastery of SMA Negeri 8 Palu. Based on these results, it implies that Kahoot Game can be applied by teachers in teaching and learning process as one of effective strategy to improve students' vocabulary mastery.